THU0348 Safety and efficacy of intravenous golimumab in adult patients with active ankylosing spondylitis: results through week 28. (15th June 2017) - Deodhar, A; Reveille, JD; Harrison, DD; Kim, L; Lo, KH; Hsia, E
Abstract : Objectives: Subcutaneous (SC) golimumab (GLM) is currently approved for adult patients (pts) with RA, PsA, and AS. The GO-ALIVE study was designed to evaluate the safety and efficacy of IV GLM in adult pts with active AS. Methods: GO-ALIVE is a Phase 3, multicenter, randomized, double-blind, placebo (PBO)-controlled trial. Pts (aged ≥18 yrs) had a diagnosis of definite AS (per modified New York criteria) and BASDAI ≥4, total back pain visual analogue scale ≥4, and CRP ≥0.3mg/dL. Pts were randomized (1:1) to IV GLM 2mg/kg at weeks (wks) 0, 4, and every 8 wks or PBO at wks 0, 4, and 12, with crossover to GLM at wk16. Up to 20% of pts could have had a prior anti-TNF agent (other than GLM), and up to 10% of pts could have complete ankylosis of the spine. The primary endpoint was ASAS20 at wk16. Major secondary endpoints were ASAS40, BASDAI50, and change in BASFI score at wk16. Some of the other statistically-controlled assessments were BASMI, and ASAS partial remission. Pts were monitored for adverse events (AEs). Data through wk28 are reported here. Results: 208 pts were randomized and received study agent (PBO: 103; GLM: 105). Baseline demographic and disease characteristics were similar between treatment groups. 78% of pts were male, mean age was 39 yrs; mean disease duration was 5.5 yrs, 89.9% were HLA-B27 positive, 5.8% had complete ankylosis of the spine, 14.4% used a prior anti-TNF. At wk16, significantly greater proportions of GLM pts vs PBO had ASAS20 (73.3% vs. 26.2%), ASAS40 (47.6% vs. 8.7%), and BASDAI 50 (41.0% vs. 14.6%) responses (all p<0.001; Table). Reductions in BASFI were also significantly greater with GLM. ASAS20 was significantly higher with GLM than PBO as early as wk2 (37.1% vs 19.4%; p=0.005). Responses in the GLM group were maintained through wk28. PBO pts who crossed over to GLM at wk16 had improvements in clinical response at wk20 that were maintained through wk28. Through wk16, 23.3% of PBO pts and 32.4% of GLM pts had ≥1 AE. Infections were the most common type of AE (PBO, 7.8%; GLM, 11.4%). Through wk28, 34.8% of all GLM-treated pts had ≥1 AE; nasopharyngitis (5.4%) was the most common. Two pts (1.0%) had SAEs (pancreatitis, n=1; pneumonia, n=1). Both were randomized to GLM. There were no opportunistic infections, malignancies, or deaths through wk28. The rate of infusion reactions was low (1.5%). 3 pts treated with GLM had 4 reactions; none was serious or severe. Conclusions: IV GLM 2mg/kg was efficacious in reducing the signs and symptoms of AS compared with PBO. GLM was well-tolerated through wk28; the safety profile was consistent with other anti-TNFs, including SC GLM. Disclosure of Interest: A. Deodhar Grant/research support from: Janssen, Amgen, Abbvie, GSK, Elli Lilly, Novartis, Pfizer, UCB, Consultant for: Janssen, Elli Lilly, Novartis, Pfizer, UCB, J. Reveille Grant/research support from: Janssen Scientific Affairs, LLC., D. Harrison Employee of: Janssen Research & Development, LLC, L. Kim Employee of: Janssen Research & Development, LLC, K. H. Lo Employee of: Janssen Research & Development, LLC, E. Hsia Employee of: Janssen Research & Development, LLC